Urban wage premium increasing with education level: Identification of agglomeration effects for Norway - Hildegunn Stokke; Jørn Rattsø; Fredrik Carlsen (European Regional Science Association (ERSA), 2012)
Income levels are higher in cities. The evidence for the income gap between urban and rural areas is overwhelming, but the agglomeration effect is hard to identify. Recent advances make use of individual level data to separate out sorting and instrumentation to handle the endogeneity of population density. We offer an analysis based on the whole working population in Norway with complete description of their education level. The data allow for estimation of the agglomeration effect for different education groups and the results show that agglomeration economies are increasing with education level. The elasticity of income with respect to population size and density is significantly lower for individuals with lower education. The result is robust to alternative instruments of urbanization and inclusion of amenity effects.
Keywords: J24; J31; J61; R12; R23; 330; Agglomeration economies; urban wage premium; sorting; education groups